THE EFFECT OF CONTENT MARKETING AND SOCIAL MEDIA INTERACTION ON REPURCHASE INTENTION OF SEA MAKEUP PRODUCTS IN TIKTOK SHOP WITH CONSUMER TRUST AS A MEDIATION VARIABLE (A STUDY ON GENERATION Z IN PALU CITY) - Yeyen Anggreni; Syamsul Bachri; Maskuri Sutomo; Farid (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of content marketing and social media interactions onrepurchase intentionSEA Makeup products on TikTok Shop with consumer trust as a mediating variable. A quantitative approach was used, using a survey method with 165 Generation Z respondents in Palu City. Data were analyzed usingPartial Least Squares Structural Equation Modeling(PLS-SEM) through the SmartPLS application. The results of the study show thatcontent marketingand social media interactions have a positive influence onrepurchase intention. Consumer trust has been shown to mediate the relationship betweencontent marketingand repurchase intention, but does not mediate the relationship between social media interactions andrepurchase intentionThis research provides theoretical contributions to the development of digital marketing studies as well as practical implications for cosmetic product promotion strategies through...social commerce platform.